Determination Of Rainfall-Runoff Characteristics In An Urban Area: Sungai Kerayong Catchment, Kuala Lumpur - Abustan, Ismail; Sulaiman, Ahmad Husaini; Abdul Wahid, Nabsiah; Baharudin, Fauzi (2008)
Rainfall-runoff characteristics of Sungai Kerayong catchment will be discussed in this article. The catchment represents an urban catchment with rapid growth rate due to urbanization process.